2014
DOI: 10.5194/bg-11-6525-2014
|View full text |Cite
|
Sign up to set email alerts
|

CO<sub>2</sub> and CH<sub>4</sub> in sea ice from a subarctic fjord under influence of riverine input

Abstract: Abstract. We present the CH 4 concentration [CH 4 ], the partial pressure of CO 2 (pCO 2 ) and the total gas content in bulk sea ice from subarctic, land-fast sea ice in the Kapisillit fjord, Greenland. Fjord systems are characterized by freshwater runoff and riverine input and based on δ 18 O data, we show that > 30 % of the surface water originated from periodic river input during ice growth. This resulted in fresher sea-ice layers with higher gas content than is typical from marine sea ice. The bulk ice [C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 73 publications
4
32
1
Order By: Relevance
“…This uptake was on the same order of magnitude as previous fluxes reported over Antarctic sea ice during the austral summer by Delille (2006) and Nomura et al (2013) and over Arctic sea ice by Semiletov et al (2004), Nomura et al (2010a, b), and Geilfus et al (2012aGeilfus et al ( , 2013, using similar chamber techniques. At the Brussels site, fluxes measured over snow were similar to those measured over bare ice, suggesting the thin snow cover had a limited impact on CO 2 exchange between the atmosphere and sea ice.…”
Section: Antarctic Sea Ice As a Springtime Sink Of Atmospheric Co 2 -supporting
confidence: 86%
See 2 more Smart Citations
“…This uptake was on the same order of magnitude as previous fluxes reported over Antarctic sea ice during the austral summer by Delille (2006) and Nomura et al (2013) and over Arctic sea ice by Semiletov et al (2004), Nomura et al (2010a, b), and Geilfus et al (2012aGeilfus et al ( , 2013, using similar chamber techniques. At the Brussels site, fluxes measured over snow were similar to those measured over bare ice, suggesting the thin snow cover had a limited impact on CO 2 exchange between the atmosphere and sea ice.…”
Section: Antarctic Sea Ice As a Springtime Sink Of Atmospheric Co 2 -supporting
confidence: 86%
“…The relationships between bulk ice pCO 2 (in µatm) and temperature measured in Antarctic (this study) and Arctic (Geilfus et al, 2012bCrabeck et al, 2014) sea ice; (b) zoom-in on the data from (a); (c) the relationships between in situ brine pCO 2 (in µatm) and brine temperature in the Antarctic (this study; Delille, 2006;Delille et al, 2007) and Arctic sea ice (Geilfus et al, 2012a); (d) relationship between the bulk ice pCO 2 (in µatm) and the brine volume fraction (in %) measured in Antarctic (this study) and Arctic (Geilfus et al, 2012bCrabeck et al, 2014) sea ice. Nomura et al (2010b), a snow cover thicker than 9 cm did not seem to completely prevent the CO 2 exchanges between the ice and the atmosphere.…”
Section: Figure 10 (A)mentioning
confidence: 79%
See 1 more Smart Citation
“…The ice characteristics in the Barrow study were similar to this Resolute Passage survey: a nearly isothermal ice cover (approaching 0 • C), low salinity in the sea ice surface layer (0-20 cm) and melt ponds at the surface of the ice (Zhou et al, 2013). Crabeck et al (2014) also reported sea ice pCO 2 [bulk] from SW Greenland. However, the concentrations reported in this work are on the lower end compared with the concentrations of 77-330 µatm reported by Crabeck et al (2014) due in part to warmer sea ice leading to a lower pCO 2 due to brine dilution by fresh meltwater (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Crabeck et al (2014) also reported sea ice pCO 2 [bulk] from SW Greenland. However, the concentrations reported in this work are on the lower end compared with the concentrations of 77-330 µatm reported by Crabeck et al (2014) due in part to warmer sea ice leading to a lower pCO 2 due to brine dilution by fresh meltwater (Fig. 5) and/or dissolution of ikaite.…”
Section: Discussionmentioning
confidence: 99%